Use of electronic services offered in the USARB Scientific Library: case study (Confluenţe Bibliologice, 2021)
The article presents the results of the research on the efficiency of ensuring access to information by the USARB Scientific Library for its users during the COVID-19 pandemic and identifies the opinion of users regarding access to information in the SL USARB during a pandemic crisis. There are also analyzed the students' answers to the questions from the online opinion poll "Access to information of SL USARB users during the pandemic crisis".
Keywords: access to information; online information resources; poll; communication technologies